Contributions to the taxonomy of Rhyncholacis (Podostemaceae): Evidence of monophyly, description of a new species, and transfer of the monotypic Macarenia - Philbrick, C. Thomas; Ruhfel, Brad R.; Bove, Claudia P. (Phytotaxa, 2018)
We conducted a phylogenetic study of neotropical subfamily Podostemoideae with a focus on Rhyncholacis and the monotypic Macarenia using molecular data (plastid: rbcL, trnL intron; nuclear: ITS). Our results placed the five included species of Rhyncholacis, one of which is newly described herein, in a moderately well supported (73 BP) clade with M. clavigera. These results support the transfer of M. clavigera to Rhyncholacis (R. clavigera); the nomenclatural changes are made. In addition, a new species of Rhyncholacis (R. paulana C.T. Philbrick & C.P. Bove) is illustrated and described. Rhyncholacis paulana is distinguished from all other species in the genus by its simple pinnately lobed leaf, which is fleshy and undulate. All other species of Rhyncholacis have leaves that are pinnately lobed, the lobes of which are repeatedly divided, or pinnately compound and characterized by finely dissected pinnate segments.